Propostas de melhoria do projeto pedagógico através do acompanhamento dos egressos - de Faria, Adriana Ferreira; de Souza Junior, Antônio Claret Rodrigues (Revista Gestão da Produção Operações e Sistemas, 2007)
The increase in the number of Production Engineering courses, in the last 6 years, was a response to the marketneeds by professionals with generalist and systemic background, capable of realizing the interactions amongthe productive processes variables and optimizing them in order to increase the competitiveness among theenterprises. The formation of high technical and methodological level professionals meeting such needs becameimperative. For this reason, it is necessary to propose modern pedagogic projects, which regard the formationof engineers to their competence, considering not only the curricular guidelines, but also the reality and thedemand of the job market. The pedagogic project should not be a ready, concluded and untouched document– conversely, it must be a dynamic instrument, constantly reviewed by the faculty, so that it can comprise changesrequired by the students as well as by the community. One of the ways of evaluating the course efficiency andidentify new market needs is through the follow-up of graduates. In this sense, this paper aims at evaluating thecurrent professional situation of the graduates in the Uniminas Product Engineering Course, as well as verifyingthe course contribution to the formation of these professionals, and identifying the strong and potential improvementaspects for the political-pedagogic project in the course.Keywords: Political-pedagogic project; Engineering teaching; Follow-up of graduates.